Being-in-the-World of the Trauma Patient: A Heideggerian Perspective. Issue 3 (May 2016) - Ekeh, Assumpta
Abstract : In his analysis of the human existence, Martin Heidegger's central focus was on teasing out the complexities intrinsic in man. He employed interrelated elements that he created to explain man's inseparability from the world. For Heidegger, a human being is never isolated but embedded completely in the world. This reality, which entails experiencing undesirable life situations, such as traumatic injuries, is viewed as an inherent part of being in the world. The trauma patient, just as any other individual in the world, is not spared of the vagaries of life at any given point in time. When the unexpected and unpleasant event happens, Heidegger suggests that life should be accepted and experienced as it is. Preoccupation with what life was prior to the unfortunate incident should be shunned. Being in the present promotes healing and positions the patient to accept the future, which leads to the road to full recovery. Personal motivation, good support systems, as well as, processes of care available in the practice environment will advance this expected goal.